Using an epistemic game to facilitate students' problem-solving: the case of hospitality management. Issue 3 (27th May 2017) - Wang, Shwu-Huey; Wang, Hsiu-Yuan
Abstract : Hospitality students are required to be able to address challenging cases or problems in the work environment. However, traditional lecture- or exam-based instruction leaves a gap between theory and practice. On the other hand, modern youth live and socialise in an increasingly digital environment, and one of their biggest pastimes is playing games. This study employs a game environment to improve students' problem-solving abilities; the purpose of this article is therefore to determine if the game is effective in this regard. This study selected two classes of hospitality management students as subjects, and randomly assigned them as the control group and the experiment group. The entire process of the study consisted of the pre-test, game training and the post-test. Only the experiment group participants were trained with the game. The quantitative and qualitative results indicate that the use of the game is beneficial in improving students' problem-solving performance.